2014
DOI: 10.9790/0853-13193037
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adenosine Deaminase Levels in Patients of Pulmonary Tuberculosis with and Without Pleural Effusion

Abstract: Tuberculosis (TB) is one of the oldest and commonest infectious diseases also known as "master of death" or "Captain of death". Pulmonary TB(PTB) and TB with pleural effusion remains a diagnostic challenge. Adenosine deaminase(ADA) is an enzyme of purine catabolism which is an inexpensive and easy test in early routine evaluation of patients with pleural effusion and helps to avoid invasive test like biopsy. Therefore, this study was aimed to determine the exact role of ADA in TB patients with and without pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(9 reference statements)
1
4
1
1
Order By: Relevance
“…in accordance with the study of Sonone et al, to avoid pleural biopsy in as much as 82% of patients as certain diagnosis of TB. [14] Against our study, Alpana et al found that On pleural fluid examination, except for ADA levels none of the variables showed a significant difference. [19] So, pleural fluid ADA level is very helpful test to rule out a tubercular etiology of pleural effusion.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…in accordance with the study of Sonone et al, to avoid pleural biopsy in as much as 82% of patients as certain diagnosis of TB. [14] Against our study, Alpana et al found that On pleural fluid examination, except for ADA levels none of the variables showed a significant difference. [19] So, pleural fluid ADA level is very helpful test to rule out a tubercular etiology of pleural effusion.…”
Section: Discussioncontrasting
confidence: 48%
“…In pathological conditions, the clearance capacity of lungs is decreased leading to increased numbers of cells in pleural fluid and the recirculation of activated T cells may cause a high serum ADA activity in patients with pulmonary disease. [14] Many studies have suggested that pleural fluid adenosine deaminase (pfADA) is useful in the diagnosis of TB-PLE. [15] The merits of using pfADA include its low cost, short turn around time, and high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our designed prediction model is the lack of samples from patients with different diagnoses, such as pneumonia, lung cancer, sarcoidosis, vasculitis, non-tuberculous mycobacterial infections, and aspergillosis. Others reported ADA (2) activity in populations of ATB, pneumonia, lung cancer, and pleural effusions of any origin with sensitivity and specificity values of ADA(2) ranging from 35% to 94% and 55% to 97%, respectively (19,20,(68)(69)(70). In addition, both CXCL10 and VEGF have been described to be potential biomarkers for various diagnoses such as chronic obstructive pulmonary disease (COPD) and non-small cell lung cancer and for exacerbations of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Tes ADA ini juga membantu dalam penegakan diagnosis dan pengobatan efusi pleura TB lebih cepat. 9 Nilai cut off ADA untuk penderita efusi pleura tuberkulosis dari berbagai penelitian bervariasi antara 30-100 IU/L dengan sensitivitas dan spesifisitas yang berbeda-beda. Perbedaan tersebut kemungkinan disebabkan karena metode analisis ADA yang berbeda, prevalensi TB yang berbeda pada setiap populasi penelitian dan karakteristik populasi penelitian yang juga berbeda.…”
Section: Pendahuluanunclassified